Wireless ultrasonic transducers for biomedical applications - Pang, Wei Ting. (2009)
A "world system" for "the transmission of electrical energy without wires" that depends upon the electrical conductivity was invented by Nikola Tesla in the early 1900s. From the idea, it triggered researchers to develop methods for moving electrical energy over “distances” without wires. Wireless is rapidly gaining in popularity for both home and business networking and this technology is continues to improve. For the reason that there exist situations where interconnecting wires are inconvenient, hazardous, or impossible, thus making wireless transmission useful and essential.